Moderate Islamic Education: A Comparative Study of Indonesia’s Insan Cendekia and Turkey’s Imam Hatip Schools - Abdul Hadi; Sarbini Anim; Hadi Yasin; Sutiono Sutiono (International Journal of Emerging Issues in Islamic Studies, 2025)
The idea of a "Clash of Civilizations" between Islam and the West has gained traction since the events of September 11, 2001. This has created a divide between two extreme viewpoints of the world, which leads to truth claims and terrorist action. Countries like Indonesia and Turkey, with large Muslim populations, play a significant role in Islamic moderate education to counter terrorism, so recently many Muslim students from various parts of the world have started going to Istanbul and Jakarta as destinations for studying Islam and are no longer only to Cairo and Medina. This is due to the relatively safe political and security conditions, and these cities' welcoming and inclusive atmosphere makes them attractive destinations for seeking a well-rounded academic experience. This research aims to compare the values of moderation in the Islamic education curricula of IHS Fatih Sultan Mehmet (Turkey) and MAN Insan Cendekia  (Indonesia), as the most excellent Islamic high school lately. Qualitative methods were used in variants of case studies, from documents, books, and interviews, and data were collected, using component analysis, and theory triangulation was used for validation. The findings reveal that both educational systems emphasize moderation, but their cultural contexts differ. In Indonesia, moderation is linked to Pancasila values, while Turkey combines secular principles with Islamic values. The result of the study shows that Islamic education in Indonesia and Turkey is classified as moderate education with different parameters. The first must adapt to local wisdom, and the second must adapt to Islamic-secular identity.